The Global Multidimensional Poverty Index 2013 - Alkire, S; Roche, J; Seth, S (Oxford Poverty & Human Development Initiative (OPHI), 2013)
The Multidimensional Poverty Index or MPI is an international poverty measure developed by the Oxford Poverty and Human Development Initiative (OPHI) for the United Nations Development Programme’s flagship Human Development Report in 2010. The innovative index reflects the multiple deprivations that a poor person faces with respect to education, health and living standards. This brief explains how the MPI is constructed and how it can be used, and summarises a number of analyses of the MPI figures published in the HDR 2013.